Gasteroid agaricomycetes of the mountain cloud forest from the Huasteca Alta Hidalguense, Mexico - Bautista-Hernández, Silvia; Raymundo, Tania; Aguirre-Acosta, Elvira; Contreras-Pacheco, Magdalena; Romero-Bautista, Leticia; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2018)
Background and Aims: The gasteroid fungi are an artificial group of fungi with closed hymenium, placed in subclasses Agaricomycetidae and Phallomycetidae of the class Agaricomycetes in the Phylum Basidiomycota. To date, a study of this group of fungi specifically for the mountain cloud forest does not exist. Hence, the aim of this paper is to study the taxonomic diversity of gasteroid Agaricomycetes from the mountain cloud forest.Methods: Between 2012 and 2015, 10 exploration trips were realized to the mountain cloud forest of the municipalities of Molango de Escamilla, Tlanchinol and Zacualtipán de Ángeles in the state of Hidalgo, Mexico. Additionally, the fungal collection of the herbarium ENCB was revised. The specimens were studied following the traditional mycological techniques, and were deposited in the herbaria ENCB and MEXU.Key results: Twenty species of gasteroid Agaricomycetes belonging to 12 genera, six families and five orders of the subclasses Agaricomycetidae and Phallomycetidae in the class Agaricomycetes were studied. Of these, Aseroë rubra, Calvatia rugosa, Laternea pusilla, Lycoperdon eximium, L. juruense, L. marginatum, L. nigrescens, Mutinus bambusinus, Scleroderma michiganense and Protubera jamaicensisare new records for Hidalgo state.Conclusions: Like other groups of fungi, the gasteroids presented a high diversity in the cloud mountain forest in the state of Hidalgo. Only 12 species had been recorded before, and in this work to additional species are mentioned for this state. Hence, it is necessary to continue with mycological explorations to improve the knowledge of the mycobiota found in this ecosystem.